Motivation and attitudes towards learning english: the case of first-year AP students in mechanical engineering at TNUT - Thi Tham, Hoang; Thi Hong, Tran (International Journal of Engineering and Technology, 2019)
The study aimed at investigating motivation and attitudes towards learning English of first-year Advanced Program students in Me-chanical Engineering at Thai Nguyen University of Technology in Vietnam. The participants were categorized into two groups accord-ing to their English proficiency. Attitude / Motivation Test Battery was employed in the study. The findings revealed that the students were motivated and held positive attitudes towards learning English. Specifically, the students of higher English proficiency had higher motivation and more highly positive attitudes towards learning English in comparison with those of lower English proficiency. Addi-tionally, the students’ motivation and attitudes were found to affect students’ beliefs, learning strategies, learning outcome, etc. Some recommendations have been introduced to help teachers develop students’ motivation and attitudes towards learning English.